Overall Infectious Complications Related to Belatacept Conversion in Comparison to Tacrolimus in Kidney Transplant Recipients. (December 2022) - Marvin, Jennifer E.; Azar, Marwan M.; Belfield, Kristen D.; Do, Vincent; Formica, Richard; Cohen, Elizabeth A.
Introduction: Belatacept has demonstrated effectiveness for preventing rejection in kidney transplant and has a favorable side effect profile. Studies assessing long-term infectious complications with belatacept compared to tacrolimus are limited.Project Aims: The purpose of this program evaluation was to determine the proportion of patients who developed an infection when converted to belatacept compared to those on tacrolimus.Design: In this retrospective evaluation, kidney transplant recipients receiving belatacept were matched 1:1 to those receiving tacrolimus, based on transplant date, age, induction immunosuppression, and cytomegalovirus risk. Data collection was initiated in tacrolimus patients on the date of belatacept conversion in the belatacept-matched patients. Data were extracted until study conclusion, death, or discontinuation of belatacept. Patients were stratified into 3 groups based on time of conversion posttransplant, which included early, late, and very late conversion. The primary outcome was the proportion of patients with an infection in belatacept compared to tacrolimus. Outcome data were calculated using chi-square, Fisher's exact test, student's t-test or Mann-Whitney U test where appropriate.Results: A total of 328 matched patients were included in the analysis. More patients on belatacept developed an infection compared to tacrolimus (42.7% vs 29.9%, P = 0.02), which was primarily driven by pneumonia (6.1% vs 0.5%; P  = 0.01). Higher incidences of infections were identified in those converted within 6 months from transplant.Conclusions: Belatacept was associated with a higher proportion of patients with infections compared to tacrolimus, particularly in those converted within 6 months from time of transplant.